Analysis of student errors in solving social arithmetic story questions for grade seven junior high school three tondano - Regar, Vivian Eleonora; Sulangi, Victor R; Rumajar, Tarmisia Sandrina Helly (Universitas Negeri Manado, 2020)
ABSTRACT. This research was conducted to find out the types of errors and the causes of students mistakes in solving social arithmetic essay questions based on Newman's procedures. This research is categorized as a descriptive research with a qualitative approach. This research was conducted at SMP Negeri 3 Tondano in the odd semester of the 2019/2020 academic year. The data in this research were sourced from the results of student work in solving social arithmetic story questions and interviews with students. Meanwhile, to analyze the data used the analysis of the side by Newman. Based on data analysis, it shows that students who make mistakes in turning problems into mathematical models (transformation error) with a presentation of 33%, students who make mistakes in writing the final answer (encoding error) with a percentage of 26%, students who make mistakes in process skills (process skill error) with a percentage of 23%, students who make mistakes at the stage of understanding the problem (comprehension error) with a percentage of 16% and students who make mistakes in reading questions (reading error) with a percentage of 2%.Â Key Words: Arithmetic Social, Students Mistakes